Using Social Media to Political Campaign in Regional Head Election East Luwu Regency - Sukmawati, Nadia; Elfiansya, Hafiz; Akbar, Muh. Randhy (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2022)
This type of research is a qualitative research using a descriptive type of approach. Sources of data obtained from primary data and secondary data through observation, interviews, documentation and literature study. The informants in this study consisted of 8 people consisting of the elected Regent, the party carrying the candidate, the candidate winning team and voters based on age category who were the people of East Luwu Regency. and data analysis through data reduction, data presentation and conclusions. The results of this study indicate four (4) indicators in the Political Campaign Strategy in the 2020 Elected Regent Network in East Luwu Regency, namely: First, the determination of communicators, the determination of communicators as directors of campaign activities in the network based on the results of joint decisions of candidates, winning teams and supporting parties who appoint Golkar party legislators as communicators at the 2020 East Luwu election. Second, Set the target target, namely the community as voters in the 2020 Luwu Timu election which is divided into several segments such as region, age, and occupation to facilitate the communication process in building support for candidates. Third, compiling messages, information related to the vision and mission, superior programs, as well as the image of the Husler-Budiman pair which are campaign materials to be conveyed to the public as voters in the 2020 East Luwu election. the winning team established social media accounts for campaign activities. Likewise, the use of online news to improve the candidate's image and the installation of billboards and distribution of campaign brochures.